Isolamento e identificação de Staphylococcus aureus e Streptococcus agalactiae de Leite Bovino - Silva, Belami Cassia da (2007)
The objective of this work was to evaluate the microbiologic and physicochemical quality of raw milk of rural estates of the micro-region of Lavras-MG. Milk samples coming from 25 herds collected from cans were analyzed, microbiological analysis such as total count of mesophyll aerobes, Staphylococcus aureus and Streptococcus agalactiae, physicochemical analyses: density, titrable acidity, fat, protein, total and non-fat solids, sodium chloride, lactose and count of somatic cells. There was no correlation between the somatic cell count and the other physicochemical variables. For the variables density, acidity, fat, total and non-fat solids, the results found were statistically equal in the different seasons analyzed. The contents of chlorites, crude and true protein was statistically different. As regards lactose, its contents were considered low for healthy cows. Staphylococcus aureus was the most isolated contagious mastitis agent due to the ease of dissemination during all the milking process, differently from Streptococcus agalactiae which is a strictly contagious pathogen. The count of mesophyll aerobes proved to be above the one allowed by the legislation at 90% of the farms. Concerning the count of somatic cells, distinct behaviors in the different seasons of the year were obtained. It follows that milk quality can be significantly improved by means of technical assistance to the farmers and adequate sanitization of milking can and utensils, enabling improved environment for milking, cooling milk on the farm and promoting its fast transportation.